Willingness of the general population to accept and pay for COVID-19 vaccination during the early stages of COVID-19 pandemic: a nationally representative survey in mainland China - Yutong Zhang; Xiaoqin Luo; Zheng Feei Ma (Taylor & Francis Group, 2021)
The COVID-19 pandemic has caused negative impacts both on populations' health worldwide. COVID-19 vaccines are currently developed and tested in clinical trials. However, limited studies have investigated the willingness to get COVID-19 vaccines in populations. Therefore, the study aimed to determine the individual's willingness to accept and pay for COVID-19 vaccines, and knowledge, attitude, and perceptions (KAP) of COVID-19 vaccines, which hopefully will be available soon. Non-pregnant Chinese adults aged ≥18 years were asked to complete a self-administered KAP COVID-19 vaccine questionnaire distributed between March and May 2020. A total of 1179 participants (574 males and 605 females) were included and the mean age was 36.0 ± 11.5 years. Both the willingness to be vaccinated against COVID-19 and pay for COVID-19 vaccines were high (77.4% and 81.1%), respectively. Also, the most acceptable price range of COVID-19 vaccine was ¥501-1000 (US $ 75-149). Education and willingness to be vaccinated were significantly associated with some of the responses in KAP (P < .05). In conclusion, our study reported high willingness to be vaccinated against COVID-19 and pay for COVID-19 vaccines in Chinese population. Our findings also provided some important contributions for public health policy makers to formulate appropriate vaccination programs.